UNDERSTANDING THE MOTIVATION BEHIND TAKAFUL PURCHASES AMONG MUSLIMS IN MALAYSIA: A STUDY OF CURRENT TAKAFUL PARTICIPANTS - Syakirah Adawiyah Ahmad Zamane; Nur Farahiah Azmi (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Despite significant growth in the Takaful industry, highlighted by the Malaysian Takaful Association’s annual report indicating an increase in Family Takaful penetration from 18.6% in 2021 to 20.1% in 2022 and a rise in net claims payout from RM 5.58 billion in 2021 to RM 7.02 billion in 2022, issues such as low public awareness, misconceptions about Takaful, and limited access to accurate information persist. There remains a need to understand the factors driving this expansion. This study addresses this gap by examining the specific motivations of Takaful participants. The interviews with Takaful participants, complemented by secondary data from articles, journals, and websites was employed in this study. Findings highlighted that four sub themes found for religiosity (riba, halal, haram, Shariah compliant), eight sub themes found for knowledge (convincing, align with Islamic, better than conventional, tranquillity, safe, campaign, social media, mass media), and four sub themes found for subjective norms (family members, community, Takaful agents, friends). As for further research, the study recommends to address these limitations of sample size, reliance on self-reported data from interviews, and limited to qualitative method, and further explore the long-term impact of the identified factors such as religiosity, knowledge, and subjective norms. These challenges must be addressed to overcome barriers to broader Takaful adoption and fully realize the industry’s growth potential.